ANALISIS KUALITAS UDARA DI KAWASAN PARKIR TRANS STUDIO MAKASSAR - Andi Dala Aprilla; rafidah rafidah (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2019)
ABSTRACT     Air pollution causes changes in the composition of air from its normal state. One of the triggers for air pollution such as Carbon Monoxide (CO) and Sulfur Dioxide (SO2). The presence of CO and SO2 in basements with a certain amount and being in a long time will disrupt human health. The objective of the research is to determine the air quality at Makassar Trans Studio. The design of the research is observational research using descriptive approach through measuring levels of carbon monoxide and sulfur dioxide using Odalog 7000. The result of the research shows that on weekdays the levels of Carbon Monoxide (CO) for daytime were 1.6 bds while at night it was 2.4 bds. While sulfur dioxide (SO2) for the daytime is 0.01 bds while at night is 0 bds. While the holiday of carbon monoxide (CO) for daytime is 3.9 bds while at night is 2.1 bds. While sulfur dioxide (SO2) for the daytime is 0.01 bds while at night is 0 bds. From these results the level of Carbon Monoxide (CO) is still below the specified quality standard (25 bds) and the levels of sulfur dioxide (SO2) are still below the standard set quality (2 bds). Based on the results of the study, it can be concluded that the air quality in parking basement of Makassar Trans Studio is still below the Threshold value according to SNI 19-0232-2005. It is recommended for the mall manager to always supervise and monitor the air filter and place the exhaust fan.